130 Early Developmental Exposure to Stress and Programming of Lifelong Gut and Immune Function. (8th October 2021) - Moeser, Adam J
Abstract: Prenatal and early postnatal life represents critical periods of development across species for many organ systems including immune, nervous, reproductive, and gastrointestinal systems. A high level of plasticity exists during these periods, and thus maternal and environmental cues including stress, immune stimulation, and nutrition, can alter the normal developmental programming of the fetus and neonate and impact the trajectory for disease risk and productivity across the lifespan. This presentation will focus on the impact of and biological mechanisms by which prenatal and early postnatal stressors, including psychological immune and nutritional stressors, alter the normal developmental programming of the immune, gastrointestinal, and neuroendocrine stress axes in the offspring and how this may link to increased disease risk and reduced productivity across the lifespan in animals and humans. Further, specifically how host factors such as biological sex interact with early life stress to shape gut and systemic neuroimmune development and later life disease risk will be discussed.